Dairy consumption and risk of functional disability in an elderly Japanese population: the Hisayama Study. Issue 6 (10th May 2019) - Yoshida, Daigo; Ohara, Tomoyuki; Hata, Jun; Shibata, Mao; Hirakawa, Yoichiro; Honda, Takanori; Uchida, Kazuhiro; Takasugi, Satoshi; Kitazono, Takanari; Kiyohara, Yutaka; Ninomiya, Toshiharu
ABSTRACT: Background: Little is known about the association between dairy intake and risk of functional disability in the elderly. Objectives: We examined the influence of dairy intake on the development of declining functional capacity and activities of daily living (ADL) in a prospective cohort study of an elderly population. Methods: A total of 859 community-dwelling Japanese residents, aged ≥65 y without functional disability, were followed up for 7 y. Functional capacity impairment was defined as a Tokyo Metropolitan Institute of Gerontology Index of Competence score of ≤12, and ADL disability was defined as a Barthel Index score of ≤95. Dairy intake was evaluated using a 150-item semiquantitative food frequency questionnaire, grouped into quartiles. The RR of dairy intake on incident functional disability was computed using a Poisson regression model. Results: The multivariable-adjusted RR of impaired functional capacity decreased significantly with increasing dairy intake levels (RR [95% CI]: quartile 1, 1.00 [reference]; quartile 2, 0.85 [0.71, 1.02]; quartile 3, 0.81 [0.68, 0.98]; and quartile 4, 0.74 [0.61, 0.90]; P -trend = 0.001). Regarding the three subscales of functional capacity, the inverse association between dairy intake and risk for impairment of intellectual activity and social role remained significant ( P -trend = 0.0009 and 0.02, respectively), but such an association was not observed for instrumental ADL. The multivariable-adjusted risk of ADL disability also decreased weakly but significantly with elevating dairy intake ( P -trend = 0.04). A similar association was seen for severity of functional disability ( P -trend = 0.002). However, the magnitude of these associations was attenuated after further adjustment for protein intake. Conclusion: Our findings suggest that higher dairy intake is associated with a lower risk of functional disability and its progression in the elderly, probably via an increase in protein intake.